Endosperm-based hybridization barriers explain the pattern of gene flow between Arabidopsis lyrata and Arabidopsis arenosa in Central Europe - Lafon-Placette, Clément (Proc Natl Acad Sci U S A, 2017)
Based on the biological species concept, two species are considered distinct if reproductive barriers prevent gene flow between them. In Central Europe, the diploid species Arabidopsis lyrata and Arabidopsis arenosa are genetically isolated, thus fitting this concept as “good species.” Nonetheless, interspecific gene flow involving their tetraploid forms has been described. The reasons for this ploidy-dependent reproductive isolation remain unknown. Here, we show that hybridization between diploid A. lyrata and A. arenosa causes mainly inviable seed formation, revealing a strong postzygotic reproductive barrier separating these two species. Although viability of hybrid seeds was impaired in both directions of hybridization, the cause for seed arrest differed. Hybridization of A. lyrata seed parents with A. arenosa pollen donors resulted in failure of endosperm cellularization, whereas the endosperm of reciprocal hybrids cellularized precociously. Endosperm cellularization failure in both hybridization directions is likely causal for the embryo arrest. Importantly, natural tetraploid A. lyrata was able to form viable hybrid seeds with diploid and tetraploid A. arenosa, associated with the reestablishment of normal endosperm cellularization. Conversely, the defects of hybrid seeds between tetraploid A. arenosa and diploid A. lyrata were aggravated. According to these results, we hypothesize that a tetraploidization event in A. lyrata allowed the production of viable hybrid seeds with A. arenosa, enabling gene flow between the two species.